2021
DOI: 10.3390/antibiotics10040400
|View full text |Cite
|
Sign up to set email alerts
|

Single DNase or Proteinase Treatment Induces Change in Composition and Structural Integrity of Multispecies Oral Biofilms

Abstract: Biofilm virulence is mainly based on its bacterial cell surrounding biofilm matrix, which contains a scaffold of exopolysaccharides, carbohydrates, proteins, lipids, and nucleic acids. Targeting these nucleid acids or proteins could enable an efficient biofilm control. Therefore, the study aimed to test the effect of deoxyribonuclease I (DNase I) and proteinase K on oral biofilms. Six-species biofilms (Streptococcus mutans, Streptococcus oralis, Actinomyces oris, Fusobacterium nucleatum, Veillonella dispar, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…In our study, we found that DNase I had no effect on P. aeruginosa or S. aureus biofilm bacterial counts in vitro and in vivo, which is in agreement with results from previous studies (Kaplan et al, 2012;Xu et al, 2015). Karygianni et al reported that DNase affects the structural integrity and spatial distribution of biofilms, and that it has no effect on the total oral bacteria CFUs (Karygianni et al, 2021). This indicates that DNase acts as an antibiofilm agent, not as an antimicrobial; moreover, clinical experience shows that DNase needs to be combined with antibiotics in the treatment of pleural empyema.…”
Section: Figure 12supporting
confidence: 93%
See 1 more Smart Citation
“…In our study, we found that DNase I had no effect on P. aeruginosa or S. aureus biofilm bacterial counts in vitro and in vivo, which is in agreement with results from previous studies (Kaplan et al, 2012;Xu et al, 2015). Karygianni et al reported that DNase affects the structural integrity and spatial distribution of biofilms, and that it has no effect on the total oral bacteria CFUs (Karygianni et al, 2021). This indicates that DNase acts as an antibiofilm agent, not as an antimicrobial; moreover, clinical experience shows that DNase needs to be combined with antibiotics in the treatment of pleural empyema.…”
Section: Figure 12supporting
confidence: 93%
“…Karygianni et al . reported that DNase affects the structural integrity and spatial distribution of biofilms, and that it has no effect on the total oral bacteria CFUs ( Karygianni et al., 2021 ). This indicates that DNase acts as an antibiofilm agent, not as an antimicrobial; moreover, clinical experience shows that DNase needs to be combined with antibiotics in the treatment of pleural empyema.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with the findings of other research groups on DNase I, which can indeed clear eDNA and achieve biofilm dispersion. [ 37,38 ] In comparison with the calcium phosphate mineralization group (CaP D ), we found that more than 50% of the eDNA was eradicated, which demonstrated that our calcium phosphate mineralization strategy could increase the activity of DNase I and enhance its eDNA cleavage function. It has also in the literature been reported that calcium cations could protect DNase I from proteolytic degradation [ 39,40 ] to maintain the long‐term DNase I release and bioactivity with Ca 2+ .…”
Section: Resultsmentioning
confidence: 87%
“…The classification criteria were the OD values according to Stepanović et al (2007) [27]. To gain insight into the possible chemical nature of the molecules involved in adhesion, the biofilm formation assay was repeated with pretreatment with proteinase K (1 mg/mL in NaCl 100 mM/Tris 200 mM buffer, pH 7.5) at 56 • C for 2 h [28,29]. Differences between the biomass of biofilms with and without proteinase K treatment were determined, and a chi-squared test (p = 0.05) was used to determine differences between the two assays.…”
Section: Adherent Phenotype Of Candida Spp Strainsmentioning
confidence: 99%